New Nanomaterials with Intrinsic Antioxidant Activity by Surface Functionalization of Niosomes with Natural Phenolic Acids - Elisabetta Mazzotta; Carla Orlando; Rita Muzzalupo (MDPI AG, 2021)
Nanoantioxidants have emerged as smart devices able to provide improved stability and biocompatibility and sustained and targeted release of conventional antioxidants. In the current research, a new family of nanoantioxidants has been developed by covalently grafting gallic (GA), caffeic (CF) and ferulic (FR) acid on the surfaces of Tween 80 niosomes. First, empty and curcumin (CUR)-loaded vesicles were prepared using a thin-layer evaporation technique and then functionalized with phenolic acids using carbodiimide chemistry. Nanoantioxidants obtained were characterized in terms of size, polydispersity index, zeta potential, and loading efficiency. Their antioxidant activity was studied by ABTS and DPPH assays. Surface functionalization of empty and CUR-loaded vesicles provided stable vesicles with intrinsic antioxidant properties. In vitro antioxidant assays highlighted that vesicles functionalized with FR or GA exhibited better antioxidant activity compared to CF-grafted niosomes. Furthermore, vesicles loaded with CUR and functionalized with GA and CF showed an enhanced scavenging ability of ABTS and DPPH radicals, compared to the single antioxidant-loaded formulations, highlighting an important synergic effect of CUR when used in combination with GA ad CF.